Hierarchy and inequality in research: Navigating the challenges of research in Ghana. (October 2022) - Mfoafo-M'Carthy, Magnus; Grischow, Jeff
This paper provides insights from experiences in data gathering and recruitment from two research projects on disability/mental health in Ghana. The focus of the study explores stigma amongst individuals diagnosed with mental illness and their caregivers. The study investigates the positioning of the researcher in a superior light by participants which often wrests power from those who should be considered the true experts of their own circumstances. Inequality in the interview process thus carried the risk of impacting the quality of the data, as some participants did not consider themselves as 'experts' of their condition. The paper explores strategies for addressing these challenges of hierarchy and inequality in the research process in the Global South. Based on the study, we report on our experiences as follows: (1) ensuring that participants are empowered to engage with researchers; and (2) training local researchers to engage in culturally sensitive research processes.